2011
DOI: 10.1007/s11064-011-0598-8
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Paradigm for Diabetic Cerebral Oedema and its Therapy: A Critical Role for Taurine and Water Channels

Abstract: The pathophysiology of cerebral oedema (CE) in diabetic ketoacidosis (DKA) remains enigmatic. We investigated the role of the idiogenic osmol taurine and aquaporin channels in an in vitro model, the SH-SY5Y neuroblastoma cell line, by sequentially mimicking DKA-like hyperglycemia/hypertonicity and hypotonic fluid therapy. Exposure to DKA-like hyperosmolarity led to shrinkage, while hypotonic fluid exposure led to cell swelling and impaired viability. Low sodium compensated in part for elevated glucose, pointin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Previous research has suggested that osmotic disequilibrium in brain cells during DKA therapy is due in part to intracellular idiogenic osmoles that are elevated to compensate for the DKA-associated hyperosmolality (33). Given the cell swelling LT data were collected from a single region of interest over the course of an experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that osmotic disequilibrium in brain cells during DKA therapy is due in part to intracellular idiogenic osmoles that are elevated to compensate for the DKA-associated hyperosmolality (33). Given the cell swelling LT data were collected from a single region of interest over the course of an experiment.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used an in vitro paradigm (33) to investigate the potential DKA therapies and membrane mechanisms contributing to cellular DKA-CE. DKA-CE occurs almost exclusively in children, typically within the first 24 h of DKA therapy (20,29).…”
Section: Discussionmentioning
confidence: 99%